Peningkatan Pendapatan Usaha Melalui Pelatihan Manajemen Resiko Pada CV Jabal Rahmat - Debbi Chyntia Ovami; Anggia Sari Lubis; Ilham Ramadhan Nasution; Dea Laila Puspita; Kiki Amalia Harahap (JPM: Jurnal Pengabdian Masyarakat, 2024)
CV Jabal Rahmat is one of the MSMEs under the guidance of the Cooperative and SME Office of North Sumatra Province, this MSME produces Puri Aren which comes from fresh sap water directly extracted by palm oil farmers without any additives and preservatives. Puri Aren is growing very rapidly, it can be seen that Puri Aren is already available in 60 supermarkets and besides that Puri Aren has exported to various countries such as Malaysia, the Netherlands and others. Seeing this very rapid development, of course, CV Jabal Rahmat needs to pay attention to managing the risks that occur in its business. Risks can occur from various aspects both environmental, financial, marketing, HR and other uncertainties which of course this will interfere with CV Jabal Rahmat's income. The focus of service objectives according to thematic and RIRN fields is the fields of social and cultural arts and education related to research topics, namely entrepreneurship, MSMEs in terms of strengthening the capacity of MSMEs to increase income from MSMEs themselves. The implementation methods carried out in this activity program are planning, implementation and sustainability. The results of this service can be concluded that the interest of CV Jabal Rahmat service participants to practice this service activity has been successful. About 70% of owners and employees attend and feel happy to take part in this training because it can add insight into risk management.